LABORATORIOS SENOSIAIN S.A. DE C.V. Primero la Familia y Después el Negocio - Espinosa Gamboa, Emilio L. (1992)
The present case is about the evolution of a family business whose beginning dates back to the early XX century. Having been a modest provincial pharmacy, over the years it became one of the most important pharmaceutical laboratories in Mexico. The main objective of the case is to detect the business strategy that has prevailed in each of the stages corresponding to the three generations of the Senosiain family and   to explore how the strategy, both familiar and business, could be modified as a vision for the future, thinking about the imminent maturity of the next generation, and considering the profound changes that could occur in the environment, both national and international. In addition, it is worth highlighting the value of the strategic definition of a company, rebuilding and analyzing its tradition and its historical development as additional elements to evaluate its forces, weaknesses, values, among others. This case may also be suitable for discussing and analyzing the peculiar problems and characteristics of family businesses.